Assessment of the dietitian's influence on the dietary habits of older adults living in Greek Islands and Cyprus. Issue 1 (21st August 2013) - Tyrovolas, Stefanos; Polychronopoulos, Evangelos; Tountas, Yannis; Panagiotakos, Demosthenes
Abstract Aim The aim of this study was to evaluate the crucial role that nutritional services provided both to public or private health‐care systems on dietary habits among older people. Methods During 2005–2009, 744 men and 742 women (>65 years) from nine Greek Islands and Cyprus Republic were voluntarily enrolled in the Mediterranean Islands study (MEDIS). Sociodemographic, clinical and lifestyle characteristics has been recorded. Information regarding practicing dietitians (n = 88) and nutritional services provided in these islands were also recorded. Results It has been demonstrated that the long‐term presence of dietitian on an island increase the adherence to the Mediterranean diet by the participants (P = 0.03). A positive association was also found between level of adherence to the Mediterranean diet by the older people and dietitian's education status (i.e. basic vs postgraduate, P = 0.003). According to the dietitians' reports, 40% of older adults have improved their dietary habits after the nutritional consultation. Conclusions Implementing nutritional services within the healthcare system seems to contribute to healthier dietary habits among older adults that may lead to a better quality of life.